An introduction to coaching skills a practical guide - van Nieuwerburgh, Christian 1971- (SAGE Publishing, 2020)
This bestselling book introduces you step-by-step to the key skills needed to become a successful coach. Supported by an Online Resource site with over 70 videos of coaching in action, this practical book will be an invaluable resource for novices and trainee coaches"--